Coding the Administrative Units of Nepal for Data Integration and Visualization (Journal on Geoinformatics, Nepal, 2019)
The value of data increases by multifold if they are presented in spatial context. For the meaningful use of data, the data table and the spatial component, the map, should be processed and prepared in such a way that they can be integrated easily. Common identification code for data and map units (point, line or polygon) is the key to this integration.